Clinical and laboratory characteristics and outcome predictors of cerebral venous sinus thrombosis in a referral neurology hospital in Bangladesh - Moniruzzaman, Md; Been Sayeed, S K Jakaria; Das, Subir Chandra; Mostafa, Md. Golam; Rashid, Md. Bazlur; Mahmud, Reaz; Akhter, Muntrasina; Mehzabin, Refat; Hossain, Sk. Md. Rubaed; Rahman, Md. Mujibur (Journal of international medical research, 2024)
Objective We aimed to describe clinical and laboratory characteristics and determine the predictors of outcome in patients with cerebral venous sinus thrombosis. Methods This prospective study was conducted over 2 years among hospitalized patients with cerebral venous sinus thrombosis. Patient outcome was assessed using the Modified Rankin Scale (mRS) score at 3 months. Outcome predictors were identified using logistic regression analysis. Results Eighty-one patients were included in this study. The median mRS outcome at 3 months was 1 (interquartile range 1–3). Poor outcomes were observed in 27.2% of patients, and the mortality rate was 9.8%. Factors associated with poor outcomes were age >60 years (relative risk [RR] 5.1), hemiparesis (RR 5.4), altered level of consciousness (RR 7.1), and transverse sinus involvement (RR 1.1). In general, mRS scores were not associated with D-dimer levels (RR 2.4). However, older patients with elevated D-dimer levels showed a significant association with poor outcomes (1.6) according to mRS scores. Conclusion Older age, hemiparesis, and altered consciousness levels were independent predictors of poor outcomes in patients with cerebral venous sinus thrombosis. High D-dimer level showed no association with functional disability, except in older patients.